Development of Lu‐177‐trastuzumab for radioimmunotherapy of HER2 expressing breast cancer and its feasibility assessment in breast cancer patients. Issue 4 (18th November 2016) - Bhusari, Priya; Vatsa, Rakhee; Singh, Gurpreet; Parmar, Madan; Bal, Amanjit; Dhawan, Devinder K.; Mittal, Bhagwant R.; Shukla, Jaya
Abstract : HER2/neu is over expressed in 20–25% of breast cancers. HER2 breast cancers are aggressive and are associated with poor prognosis. The aim of this study was to develop the clinical grade Lu‐177‐trastuzumab and its preliminary evaluation for specific tumor targeting in HER2 positive breast cancer patients. Trastuzumab was conjugated to bifunctional chelator, DOTA, and characterized for integrity and the number of molecules conjugated. Radiolabeling of DOTA‐conjugated trastuzumab was optimized using Lu‐177. Quality control parameters including radiochemical purity, stability, sterility, pyrogenicity and immunoreactivity were assessed. A preliminary pilot study was conducted on breast cancer patients ( n  = 6 HER2 positive and n  = 4 HER2 negative) to evaluate the ability of Lu‐177‐trastuzumab for HER2 specific tumor targeting. The conjugates were efficiently labeled with Lu‐177 with high radiochemical purity (up to 91%) and specific activity (6–13 µCi/µg). Lu‐177‐trastuzumab was stable up to 12 hr post labeling. The radioimmunoassay demonstrated good antigen binding ability and specificity for HER2 receptor protein. The patient studies showed the localization of Lu‐177‐trastuzumab at primary as well as metastatic sites (HER2 positive) in the planar and SPECT/CT images. No tracer uptake was observed in HER2 negative patients that indicated the specificity of Lu‐177‐trastuzumab. The study demonstrated that in‐house developed Lu‐177‐trastuzumab has specific targeting ability for HER2 expressing lesions and may in future become a palliative treatment option in the form of targeted radionuclide therapy for disseminated HER2 positive breast cancer. Abstract : What's new? A promising treatment strategy for aggressive, HER2‐positive breast cancers involves the attachment of radioactive molecules to monoclonal antibodies. In this study, the authors attached radioactive lutetium‐177 (Lu‐177) to the anti‐HER2 drug trastuzumab. In tests on patients with both HER2‐positive and negative cancers, this new combination molecule specifically targeted only HER2‐positive primary tumors and metastases. Future studies will determine whether Lu‐177‐trastuzumab is an effective treatment option; in the meantime, it may be a useful palliative agent and may contribute to improved quality of life for these patients.